2021
DOI: 10.1016/j.jss.2020.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the Effect of Age on In-hospital Burn Mortality in a Resource-Limited Setting

Abstract: Background: This global burden of burn injury is suffered disproportionately by people in low-income and middle-income countries, where 70% of all burns occur. Models based in high-income countries to prognosticate burn mortality treat age as a linearly increasing risk factor. It is unclear whether this relationship is similar in resource-limited settings. Methods: We analyzed patients from the Kamuzu Central Hospital Burn Registry in Lilongwe, Malawi, from 2011 to 2019. We examined the relationship between bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Regarding skin trauma, elderly patients are more likely to bear the skin pain caused by it and are also more susceptible to skin trauma. It is easy to adapt to the pain after surgery, which is consistent with the results of the present research (26,27).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding skin trauma, elderly patients are more likely to bear the skin pain caused by it and are also more susceptible to skin trauma. It is easy to adapt to the pain after surgery, which is consistent with the results of the present research (26,27).…”
Section: Discussionsupporting
confidence: 92%
“…Our study also showed that the youngest pediatric patients had a higher mortality risk with early excision and grafting. We previously showed that infants and toddlers have a higher mortality rate than older children in Malawi, even when controlling for burn size [19]. Our study proves that mortality is higher in younger pediatric burn patients who undergo early excision in this resource‐limited setting.…”
Section: Discussionsupporting
confidence: 63%
“…Age was treated as a categorical variable based on previous data from our center. [15] Reliable burn depth data is not available, so the presence of a flame burn was used as a surrogate for deeper burns. We then systematically used a change-in-effect methodology, removing potential confounders if they did not significantly change the relationship (< 10% change) between pandemic presentation and mortality.…”
Section: Methodsmentioning
confidence: 99%